"Do Your Homework": hegemonic discourses on work, in the tabloid media, during the Eurozone Crisis - Baptista, Maria Manuel (2020)
This article explores hegemonic discourses on productive work and labor, in the context of the Eurozone crisis. Based on the separation between creditor and debtor countries, often associated with Northern and Southern Europe, the coverage of the Portuguese legislative elections of 2011, in the online versions of two tabloid newspapers, the German Bild and the Portuguese Correio da Manhã, was analyzed. The analysis allowed us to identify a hegemonic discourse, transversal to both newspapers, that places work and the consequent accumulation of capital, as the central axis of valuing a society, dividing Europe into compliant (trustworthy) and non-compliant (untrustworthy) countries. In a few instances, we have identiﬁed a counter-hegemonic discourse, that values elements beyond productivity, calls into question the need for compliance, and places the root of the crisis in the very system that values development, as promoted in advanced capitalism.